Diagnostic Value of Direct Antibiotic Susceptibility Test for Faster BacterialSusceptibility Reporting in Bacteremia - Hapsari, Rebriarina; Ciptaningtyas, Vincentia Rizke; Masfiyah, Masfiyah (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2012)
Background: Rapid and accurate information on susceptibility of bacteria causing bacteraemia is very helpful in sepsis management. Blood culture is the gold standard for bacteraemia diagnosis. Standard antibiotic susceptibility testing needs at least three days for completion while direct method can give the result a day earlier. The aim of this study was to investigate the diagnostic value of direct antibiotic susceptibility testing in blood culture.Methods: Bloods from positive BACTEC bottles which met inclusion and exclusion criteria were put into sterile tubes and centrifuged. The pellets were then used to make 0.5 McFarland bacterial suspensions and directly used for antibiotic susceptibility testing. Interpretations of direct method were compared to standard method to count sensitivity, specificity, sensitive predictive value, resistant predictive value, accuracy, and kappa value.Results: From 58 samples (containing 22 gram negative, 36 gram positive bacteria), there were 309 total antibiotic susceptibility tests. Direct method showed sensitivity, specificity, sensitive predictive value, resistant predictive value, accuracy, and kappa value of 89.3%, 92.9%, 93.8%, 87.8%, 86.4%, and 0.82, respectively.Conclusion: Direct antibiotic susceptibility testing has a good agreement with the standard method so it can aid faster antibiotic susceptibility reporting in bacteraemia (Sains Medika, 4(2):174-181).